Effect of consumption of mixed herbs & spices in case controlled type 2 Diabetes Mellitus (T2DM) patients - Mahmood, Tahir; Khattak, Muhammad Muzaffar Ali Khan; Mohd Shukri, Nor Azwani; Zulkifli , Hidayatul Hafidzah; Azam , Siti Amirah (2014)
Herbs and spices are believed to possess hypoglycemic effects in Type 2 Diabetes Mellitus (T2DM) patients. Twenty patients were recruited from the Medical Outpatient Department of Hospital Tengku Ampuan Afzan (HTAA) in Pahang, Malaysia. Ten patients were provided with placebo while the other 10 patients received four gram of mixed herbs and spices for 30 days. Blood samples were collected before and at the end of the feeding period. These samples were analyzed for parameters namely fasting blood glucose (FBG), glycosylated haemoglobin (HbA1c) and lipid profile concentration. The result shows that there was a significant (P<0.05) reduction in the fasting blood glucose and glycosylated haemoglobin, HbA1c blood lipid profile remained unchanged. The present study indicates that the mixed herbs & spices tested in this clinical trial have some efficacy for hyperglycemia control .